2015
DOI: 10.1111/hex.12382
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of cervical cancer risk factors and symptoms: cross‐sectional community survey in post‐conflict northern Uganda

Abstract: BackgroundLack of awareness of risk factors and symptoms for cancer may lead to late diagnosis and poor prognosis.ObjectiveWe assessed community awareness about cervical cancer risk factors and symptoms and perceptions about prevention and cure of cervical cancer in order to contribute data to inform interventions to improve cervical cancer survival.DesignCross‐sectional population‐based survey.Setting and participantsWe conducted this study in Gulu, a post‐conflict district in Uganda in 2012. The sample inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
102
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 68 publications
11
102
4
1
Order By: Relevance
“…Having ever heard about cervical cancer was found to be high in other studies in urban and peri-urban areas such in Dares Salaam and Kerala, with prevalence of 53.0% and 74.2%, respectively [27,30]. In rural Uganda, two recent studies in Masaka [6] and northern Uganda [7] showed that more than 90% of participants had ever heard about cervical cancer. The study in Northern Uganda however included both male and female unlike our current study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Having ever heard about cervical cancer was found to be high in other studies in urban and peri-urban areas such in Dares Salaam and Kerala, with prevalence of 53.0% and 74.2%, respectively [27,30]. In rural Uganda, two recent studies in Masaka [6] and northern Uganda [7] showed that more than 90% of participants had ever heard about cervical cancer. The study in Northern Uganda however included both male and female unlike our current study.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, only 54.0% acknowledged that having sexual intercourse with uncircumcised men increases a woman's risk for developing cervical cancer. Similarly, low levels of HPV awareness was also found in northern, eastern Uganda and Botswana [7,29,31,32]. Clearly this widespread low levels of awareness about the HPV and vaccination against the HPV as primary control measure for cervical cancer is concerning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study conducted in China, 22.1% and 13.3% of the study population had heard of HPV and HPV vaccine respectively. 6 The knowledge level about cervical cancer was low among the participants in spite of the introduction of National Cancer Control Programme in India. This is probably because of the lack of awareness of cervical cancer and its screening methods which is available in the nearby primary health care facilities.…”
Section: Discussionmentioning
confidence: 98%